2018
DOI: 10.1093/mnras/sty2363
|View full text |Cite
|
Sign up to set email alerts
|

Absolute colours and phase coefficients of trans-Neptunian objects: HV − HR and relative phase coefficients

Abstract: The trans-Neptunian objects (TNOs) are small Solar System bodies at large distances from the Sun. As such, their physical properties are difficult to measure. Accurate determination of their physical parameters is essential to model and theorize the actual composition and distribution of the population, and to improve our understanding of the formation and evolution of the Solar System. The objective of this work is to construct phase curves in two filters, V and R, of a large TNO sample obtaining absolute mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…In Fig. 17 we show the absolute colors vs. the difference in G. There seem to be weak anticorrelations (see Table 6) between these quantities, possibly analogous to these found for TNOs (Ayala-Loera et al 2018;Alvarez-Candal et al 2019). In the latter work, we proposed it was related to a predominance of single-scattering at a low-phase angle, but the same cannot be said here because, first, G is not the same as the phase coefficient β obtained from a simple linear model, and second, the PCs in this work are mostly of asteroids obtained at a wide range of phase angles (see the right panel of Fig.…”
Section: Absolute Colors and ∆Gsupporting
confidence: 59%
See 1 more Smart Citation
“…In Fig. 17 we show the absolute colors vs. the difference in G. There seem to be weak anticorrelations (see Table 6) between these quantities, possibly analogous to these found for TNOs (Ayala-Loera et al 2018;Alvarez-Candal et al 2019). In the latter work, we proposed it was related to a predominance of single-scattering at a low-phase angle, but the same cannot be said here because, first, G is not the same as the phase coefficient β obtained from a simple linear model, and second, the PCs in this work are mostly of asteroids obtained at a wide range of phase angles (see the right panel of Fig.…”
Section: Absolute Colors and ∆Gsupporting
confidence: 59%
“…We generated 10 000 different solutions of the PCs for each run by varying each magnitude within their errors following m * = m + rand i , where rand i is a random number extracted from a normal distribution with σ = σ m . This is based on the method developed and tested in Alvarez-Candal et al (2016 and Ayala-Loera et al (2018) for TNOs. Note that it may happen that some of the 10 000 runs resulted in non-valid solutions.…”
Section: First Testmentioning
confidence: 99%
“…(1) In Ayala-Loera et al (2018) we identified a strong relation between the absolute colour and the relative phase coefficients for a sample of 106 objects, this relationship holds regardless of location in the outer Solar System and size. In this work we confirm that it is present among the different dynamical classes, therefore, it must be a property of the particles forming the surface of the bodies, rather than composition, perhaps due to the size-particle distribution and/or inter-particle spacing.…”
Section: Discussionmentioning
confidence: 91%
“…Similar diversity was reported by Rabinowitz et al (2007), who also noted that the phase functions of Centaurs tend to be linear with α. Additional phase function measurements, also showing a wide scatter, are given in Alvarez-Candal et al (2016) and Ayala-Loera et al (2018). Motivated by these results, and in the interests of simplicity, we write 2.5 log 10 (Φ(α)) = −βα, where β = 0.061±0.002 magnitudes per degree is the mean value of the V-filter phase coefficients reported for seven Centaurs in Table 4 of Rabinowitz et al (2007).…”
Section: Photometrymentioning
confidence: 93%